PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENTS MENGGUNAKAN FLASHCARD SEBAGAI UPAYA PENINGKATAN SOFTSKILL DAN HASIL BELAJAR SISWA SD - Mohammad Edy Nurtamam; Ariesta Kartika Sari (Widyagogik, 2016)
This research intends to describe the students’ responses toward the application of cooperative learning, especially Teams Games Tournaments (TGT) using flashcard, and to know the development of students’ soft skills in learning. Moreover, this research also intends to know the difference of learning results of students in elementary school after using TGT and conventional learning. This research conducted at Pejagan 5 Elementary School in Bangkalan. The sample of this research is elementary school students, grade five, especially in math subjects. The research method in this research is experimental research, starting with making lesson plan and worksheets for a group work, and learning evaluation. The research instrument consists of students’ questionnaire, students’ worksheet and learning evaluation. Based on the result of this research, it can be conclude that there is no significant differences between learning using cooperative learning TGT type using flashcard and using conventional learning. However, classical target in experiment group is better than control group which reaches 90%. Moreover, students’ response toward this learning is very good, the presentation shows that 95,3% students’’ soft skills increase up to 16 point in twice meeting. And in the last lesson, the students’ soft skills develop well and also there is a significant difference between TGT groups learning using flashcard with conventional group learning